Subordinates as threats to leaders - Amihai Glazer; Björn Segendorff (Stockholm School of Economics, The Economic Research Institute (EFI), 2001)
A leader of an organization may view a subordinate as threatening or weakening the leader's position. The threat may increase with the subordinate's ability and reduce the rents the leader wins. In particular, a leader who trains his subordinate reduces the cost to the owner of a firm in replacing the leader, and so reduces the leader's bargaining power. The leader therefore provides inefficiently low training for the subordinate.
Keywords: C72; D72; D82; J33; 330; Leader; Subordinate; Threat; Training; Bargaining